A multilobulated asymptomatic umbilical nodule revealing endometriosis. Issue 3 (12th January 2021) - Chamli, Amal; Souissi, Asmahene; Alaoui, Fatima; Chelly, Ines; Eleuch, Dalenda; Mokni, Mourad
Abstract: Primary umbilical endometriosis is unusual clinical presentation of endometriosis. Its diagnosis can be challenging due to lack of knowledge. This condition should be listed in the differential diagnosis of umbilical disorders. Abstract : Primary umbilical endometriosis is unusual clinical presentation of endometriosis. Its diagnosis can be challenging due to lack of knowledge. This condition should be listed in the differential diagnosis of umbilical disorders.